Status Gizi Ibu Hamil Berdasarkan Pengukuran Lingkar Lengan Atas (LILA) - Febri Adriati; Shanty Chloranyta (Jurnal Kesehatan Panca Bhakti Lampung (JKPBL), 2022)
Maternal mortality rate is one of indicators to see health effort success. The target of global maternal mortality rate according to Sustainable Development Goals (SDGs) is 70/100,000 live births. Maternal Mortality rate in Indonesia is still at upper score of SDGs target. Bleeding is one of main causes of maternal mortalities in Lampung province. Bleeding can be caused by anemia in pregnancy, where pregnant mother’s nutritional status affects anemia case. One of methods to determine the pregnant mother’s nutritional status is by mid-supper arm circumference measurement. The objective of this research is to find out the pregnant mother’s nutritional status based on the mid-supper arm circumference measurement. This is a descriptive quantitative research with cross sectional approach. Population is all 35 pregnant mothers visiting for antenatal care in Kharisma Midwife Clinic in Panjang in Bandar Lampung in July 2022. Samples are of total population. The research result shows that 91,4% respondents show good pregnant mother’s nutritional status and 8,6% respondent show malnutrition status.